Gregarious caterpillars shorten their larval development time in response to simulated predation threat. (14th June 2022) - Cisternas, Mónica F.; Ríos, Rodrigo S.; Gianoli, Ernesto
Abstract: Group living in gregarious caterpillars may shorten the larval stage, which is thought to reduce predation exposure. In the gregarious caterpillar Battus polydamas archidamas (Papilionidae) we addressed the effects of simulated predation threat on the duration of the larval stage in solitary and gregarious caterpillars. We further evaluated the consequences of group rearing and predation stimuli for pupal mass. We reared caterpillars singly and in groups of ten individuals. Caterpillars were subjected to simulated predation threats (prodding with a paintbrush) and control larvae were untouched. We determined larval stage duration and pupal mass. We also recorded in solitary and gregarious caterpillars the proportion of individuals reacting to predation threats with distinct behavioural responses. Caterpillars in the group completed larval development earlier than solitary caterpillars. This pattern of accelerated development was already evident in the first instar. Simulated predation reduced the duration of both the entire larval stage and the first instar, but only for caterpillars in the group. Pupal mass was not affected by the predation treatment in either solitary or gregarious caterpillars. Solitary caterpillars showed thrashing and osmeterium display + thrashing more frequently than gregarious caterpillars, while individuals in the group reacted with osmeterium display to a greater extent. Accelerated larval development in response to predation risk has been predicted by theoretical models, but–to our knowledge–this is the first report on gregarious caterpillars. This putative adaptive response did not entail a fitness cost in terms of pupal mass. Abstract : In the gregarious caterpillar Battus polydamas archidamas (Papilionidae), simulated predation threat led to accelerated development only for caterpillars in group (10 individuals).